The SAGE handbook of social studies in health and medicine - Scrimshaw, Susan C.; Lane,Sandra D.; Rubinstein,Robert A.; Fisher,Julian (London : SAGE Publications Ltd, 2022)
With new chapters on key topics such as mental health, the environment, race, ethnicity and health, and pharmaceuticals, this new edition maintains its multidisciplinary framework and bridges the gap between health policy and the sociology of health. It builds upon the success of the first by encompassing a range of issues, studies, and disciplines. The broad coverage of topics in addition to new chapters present an engagement with contemporary issues, resulting in a valuable teaching aid. This second edition brings together a diverse range of leading international scholars with contributors from Australia, Puerto-Rico, USA, Guatemala, Germany, Sri Lanka, Botswana, UK, South Sudan, Mexico, South Korea, Canada and more. The second edition of this Handbook remains a key resource for undergraduates, post-graduates, and researchers across multidisciplinary backgrounds including: medicine, health and social care, sociology, and anthropology. Part One: Culture, Society and Health; Part Two: Lived Experiences; Part Three: Health Care Systems, Access and Use; and Part Four: Health in Environmental and Planetary Context.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Social medicine